Pengaruh Lama Fermentasi Terhadap Kadar Alkohol dan Tingkat Kesukaan Wine Sorgum (Sorghum bicolor l. Moench) - Nge, Sonya Titin; Ballo, Apriliana (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 7 No 2 (2022), 2022)
Wine is a drink made through the fermentation process of sugar in grapes which is then converted into alcohol. Apart from grapes there is another alternative for wine making, namely sorghum seeds. The starch content in sorghum seeds can be used in wine making. The purpose of this study was to determine the effect of fermentation time on alcohol content and level of preference for sorghum wine. This research was conducted at the Laboratory of Biological Education, Artha Wacana Christian University, Kupang, using the RAL experimental method with 4 treatments and 4 repetitions. Wine is made by mixing sorghum seed extract with yeast. The treatment of fermentation time in this study was P1 (7 days), P2 (14 days), P3 (21 days) and P0 / control (5 days). The resulting wine will be tested for alcohol content using an alcohol meter and an organoleptic test to determine the panelists' preference for sorghum wine. Data analysis using ANOVA and further Duncan / DMRT test. The results showed that the highest alcohol content was in the P3 treatment with an average of 8.75%. Overall, the parameters of taste, aroma and color have a significant effect. The data showed that the average panelists preferred the P3 treatment of taste (3,41), aroma (3,55), and color (3,38). Thus sorghum seeds can be an alternative ingredient in sorghum wine making.